Financial Constraints and Growth: Multinational and Local Firm Responses to Currency Depreciations - Desai, Mihir A.; Foley, C. Fritz; Forbes, Kristin J. (Review of Financial Studies, 2008)
This article examines how financial constraints and product market exposures determine the response of multinational and local firms to sharp depreciations. U.S. multinational affiliates increase sales, assets, and investment significantly more than local firms during, and subsequent to, depreciations. Differing product market exposures do not explain these differences in performance. Instead, a differential ability to circumvent financial constraints is a significant determinant of the observed differences in investment responses. Multinational affiliates also access parent equity when local firms are most constrained. These results indicate another role for foreign direct investment in emerging markets–multinational affiliates expand economic activity during currency crises when local firms are most constrained. The Author 2007. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please email: journals.permissions@oxfordjournals.org., Oxford University Press.